Pengaruh Harga dan Fasilitas terhadap Minat Sewa Kost yang Berdampak pada Prestasi Belajar Mahasiswa di Yogyakarta - Denok Sunarsi; Akhmar Barsah; H. Hastono; Irfan Rizka Akbar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to determine the effect of price and facilities on boarding rent interest which has an impact on student achievement in Yogyakarta. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the price has a significant effect on interest in lease by 37.0%, the hypothesis test obtained t count> t table or (7.590> 1.984). Facilities have a significant effect on rental interest by 48.9%, hypothesis testing is obtained t count> t table or (9.677> 1.984).  Price and facilities simultaneously have a significant effect on rental interest with the regression equation Y = 9.005 + 0.274X1 + 0.514X2 and the contribution of the effect is 55.5%, the hypothesis test obtained F count> F table or (60.568> 2,699). Rental interest has a significant effect on student achievement by 39.8%, hypothesis testing is obtained t count> t table or (8,051> 1,984)